PENEMUAN MUHAMMAD BIN MUSA AL KHAWARIZMI - Aldewo Dillon Perkasa; Mohammad Luthfan Faohan; Kania Dewi; Galuh Inti Aulia; Hisny Fajrusallam (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2021)
Abstract - This study aims to examine the findings of an Islamic scientist named Al Khwarizmi or better known as